Improving Student Creativity Activeness And Implementation Approach In Cbsa On Civics Lesson Grade Ii Sd Negeri 39 Lengayang Gompong.Kec Markets Academic Year 2016/2017 - Darleli Darleli (Fakultas Sastra Universitas Ekasakti, 2017)
The purpose of this study is to prove that the use of the environment around the school can improve students' understanding of the subject Civic Education in Elementary School student 39 Class II Gompong Market. This study uses a class action approach. The study population was taken of all students in grade II , the data collection techniques used artificial teacher learning achievement test. Actions performed a total of two cycles. Data analysis techniques used analysis of the percentage of change in the results of the evaluation study before and after tutoring services with peer tutors. Thus there is an increase in students' mastery of the first cycle and the second cycle. Based on the above, it can be made a conclusion as follows: